Socio-Geography of Human Mobility: A Study Using Longitudinal Mobile Phone Data - Phithakkitnukoon, Santi (Public Library of Science, 2012)
A relationship between people’s mobility and their social networks is presented based on an analysis of calling and mobility traces for one year of anonymized call detail records of over one million mobile phone users in Portugal. We find that about 80% of places visited are within just 20km of their nearest (geographical) social ties’ locations. This figure rises to 90% at a ‘geo-social radius’ of 45km. In terms of their travel scope, people are geographically closer to their weak ties than strong ties. Specifically, they are 15% more likely to be at some distance away from their weak ties than strong ties. The likelihood of being at some distance from social ties increases with the population density, and the rates of increase are higher for shorter geo-social radii. In addition, we find that area population density is indicative of geo-social radius where denser areas imply shorter radii. For example, in urban areas such as Lisbon and Porto, the geo-social radius is approximately 7km and this increases to approximately 15km for less densely populated areas such as Parades and Santa Maria da Feira.